The unexpected discovery of blind snakes (Serpentes: Typhlopidae) in Micronesia: two new species of Ramphotyphlops from the Caroline Islands - Wynn, Addison H.; Reynolds, Robert P.; Buden, Donald W.; Falanruw, Marjorie; Lynch, Brian (Zootaxa, 2012)
Two new blind snakes in the genus Ramphotyphlops are described from Ulithi (R. hatmaliyeb sp. nov.) and Ant Atoll (R.adocetus sp. nov.) in the Caroline Islands, the first blind snake species known from Micronesia east of Palau (excludingRamphotyphlops braminus). Both species are unusual in being known only from small, low-lying atolls. They can be dis-tinguished from other Ramphotyphlops by the combination of 22 scale rows over the length of the body; a wedge-shaped snout, without a keratinized keel; and a broad, pyriform (R. adocetus) or ovate (R. hatmaliyeb) rostral scale.